Long-term damage to the ENT system in Wegener's granulomatosis. - Martinez Del Pero, M; Walsh, M; Luqmani, R; Flossmann, O; Mukhtyar, C; Jani, P; Rasmussen, N; Jayne, D (2011)
The objectives of the study are to describe long-term ENT damage and assess risk factors in patients with newly diagnosed and treated Wegener's granulomatosis (WG) using the vasculitis damage index (VDI). Data from four randomised controlled trials carried out by the European Vasculitis Study Group was used. Patients newly diagnosed with WG with complete data at 5 years were included. Patients enrolled into the trials without 5-year data were excluded. Total and ENT VDI scores were recorded at 12 months and after at least 5 years. Logistic regression models were constructed to assess risk factors using total ENT and overall VDI score over the follow-up period, the proportion of patients with increased VDI score and the presence or absence of damage as the main outcomes. One hundred and thirty-eight patients were included. Ninety patients (65%) had long-term damage and 81% of these (73/90) developed some damage in the first 12 months. Positive ENT activity score (BVAS) at baseline and relapses were associated with higher ENT VDI scores long-term (OR = 6.90, 95% CI 2.01-23.75; OR = 2.65, 95% CI 1.20-5.82). Increasing BVAS score showed a trend towards lower VDI scores (OR = 0.93, 95% CI 0.88-0.99). Only ENT relapses and number of relapses were associated with an increase in VDI over time (OR = 8.38, 95% CI 3.10-22.68; OR = 1.79, 95% CI 1.24-2.58). In conclusion, most of the ENT damage in these patients was accrued within 12 months of diagnosis. We have shown an association between later ENT damage and the presence of ENT disease at baseline; lower initial BVAS and higher rate of disease relapse.